Dialectic evolution through the social innovation process: From microcredit to microfinance - Arvind Ashta; Mawuli Couchoro; Abu Saleh Musa (Journal of Innovation and Entrepreneurship, 2014)
Microfinance is the provision of financial services to the financially excluded, usually the poor. We use literature reviews and descriptive research to present different aspects of the relationship of the microfinancial services to microenterprise. The first thrust in this field had been from microcredit and group lending to encourage business initiatives among the poor. The hope that these services would lift them out of poverty had largely built the brand image of the sector. However, the spread of consumer microcredit and uncontrolled growth of microfinance led to over-lending without adequate checks and balances, leading to over-indebtedness and associated stress, and critique of microcredit. To restore balance, other financial products, such as microequity, microsavings, microinsurance, microguarantees, and microremittances, have been suggested. We place these developments in a social innovation process perspective by showing that microfinance, through its wide range of innovatively distributed products, can be a key factor to foster entrepreneurship.
Keywords: L26; O16; O17; O30; 650; Entrepreneurship; Microcredit; Microequity; Microinsurance; Microsavings; Microremittances; Microguarantee; Innovation